2013
DOI: 10.1080/02508281.2013.11081754
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Content of Pictures of Animals in Tourism Promotion

Abstract: Based on the animal ethics approaches of utilitarianism, animal rights and eco-feminism, this study reflects on the inclusion of animals in the tourism experience, more specifically, the use of promotional pictures of animals. The aim is to identify how the conceptualization of animals can be understood in relation to various animal ethics approaches and the local culture. An empirical case-study from northern Norway is investigated. The results show that the inclusion of animals in the tourism experience is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 42 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Recently, some tourism scholars have discussed the use of animals in tourism from an ethical perspective, and some have explicitly adopted and discussed the Ecofeminism approach (Bertella, 2013, 2014, 2017, 2018; Burns, 2015, 2017; Burns et al , 2011; Cohen, 2009; Fennell, 2012a, 2012b, 2012c, 2013a, 2013b; 2014; Markwell, 2015; Shani and Pizam, 2008; Yudina and Fennell, 2013; Yudina and Grimwood, 2015). With regard to wildlife tourism, Yudina and Grimwood (2015, p. 731) investigate polar bear watching.…”
Section: Wild Animals From An Ecofeminist Perspectivementioning
confidence: 99%
“…Recently, some tourism scholars have discussed the use of animals in tourism from an ethical perspective, and some have explicitly adopted and discussed the Ecofeminism approach (Bertella, 2013, 2014, 2017, 2018; Burns, 2015, 2017; Burns et al , 2011; Cohen, 2009; Fennell, 2012a, 2012b, 2012c, 2013a, 2013b; 2014; Markwell, 2015; Shani and Pizam, 2008; Yudina and Fennell, 2013; Yudina and Grimwood, 2015). With regard to wildlife tourism, Yudina and Grimwood (2015, p. 731) investigate polar bear watching.…”
Section: Wild Animals From An Ecofeminist Perspectivementioning
confidence: 99%
“…As Labatut et al (2016) have observed, nonhuman animals have always been largely ignored by the field of management and organization studies, a situation they attribute to a purported lack of reason and, therefore, capacity for agency. As always, of course, this is not to suggest that non-human animals have been entirely excluded from more general considerations as either organizational resources, or actants within a particular labour process (Bertella 2013;Bright 1986;Coulter 2016;Nocella et al 2013;Tremblay 2002: or as objects of ethical interest, especially in tourism (Burns 2015;Hoarau-Heemstra 2018;Hughes 2001;Fennell 2012Fennell , 2013). Nonetheless, the field remains a relatively embryonic one.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive academic research has explored animal consumption in tourism (e.g. Bertella, 2013;Fennell, 2012;Fennell & Bowyer, 2020;Yudina & Fennell, 2013); however, the industry apparently has yet to learn how to effectively manage emerging public health crises potentially attributable to wild animal consumption.…”
Section: Introduction and The 2019 Novel Coronavirus Pneumonia Outbreakmentioning
confidence: 99%